Startkapital - Heynen, Julian; Kreuzer, Stefanie; Zweite, Armin; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
Armaly, Fareed ; Becher, Bernd & Hilla ; Beuys, Joseph ; Broodthaers, Marcel ; Buren, Daniel ; Byars, James Lee ; Chin, Mel ; Eliasson, Olafur ; Fisher, Morgan ; Fritsch, Katharina ; Förg, Gunther ; Gala Committee ; General Idea ; Gillick, Liam ; Gober, Robert ; Goldstein, Jack ; Goldstein, Zvi ; Graham, Dan ; Gursky, Andreas ; Hamilton, Richard ; Hawkins, Richard ; Herold, Georg ; Honert, Martin ; Huws, Bethan ; Höfer, Candida ; Kabakov, Ilya ; Kawara, On ; Kelley, Mike ; Kim, Soo-Ja ; Kippenberger, Martin ; Knoebel, Imi ; Korine, Harmony ; Kounellis, Jannis ; Leonard, Zoe ; Levine, Sherrie ; Mason, T. Kelly ; McCarthy, Paul ; Metzel, Olaf ; Miller, John ; Morley, Ivan ; Mucha, Reinhard ; Mueck, Ron ; Muñoz, Juan ; Oursler, Tony ; Paik, Nam June ; Pardo, Jorge ; Pettibon, Raymond ; Pfeiffer, Paul ; Pistoletto, Michelangelo ; Plessen, Magnus ; Polke, Sigmar ; Popp, Markus ; Rhoades, Jason ; Ruff, Thomas ; Schneider, Gregor ; Schütte, Thomas ; Slominski, Andreas ; Stockhausen, Karlheinz ; Struth, Thomas ; Tompkins, Hayley ; Trockel, Rosemarie ; Tuymans, Luc ; Viola, Bill ; Wall, Jeff ; Weiner, Lawrence ; Welling, James ; West, Franz
Engels
Startkapital, K21 Kunstsammlung Nordrhein-Westfalen Düsseldorf, 19.04.2002 - 27.04.2003
boek
Keywords: Düsseldorf